2013
DOI: 10.5861/ijrse.2014.642
|View full text |Cite
|
Sign up to set email alerts
|

Mandates, needs, equitable resources, and current research in English language teacher education: The case of Turkey

Abstract: Improving the quality of English language teacher education (ELTE) programs has become a major point of consideration; however, such programmatic evaluations are markedly rare.This study utilizes both numeric and interpretive qualitative data in a blended research design. The study addresses, vis-à-vis current research in related fields: What is the current situation of the Turkish ELTE programs in terms of curriculum strength and faculty resources? How do the program directors and teacher candidates envision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…For instance, in Atay's (2005) study, Turkish prospective teachers of English regarded having native-like competence as the main purpose of English language teaching, and reported that having a native teacher is more advantageous in order to develop a native-like accent. From a different perspective, exploring English language teacher education programs in Turkey, Cepik and Polat (2014) claimed that teacher educators expect teachers to have near-native proficiency in English. Confirming the results of Atay (2005) and Cepik and Polat's (2014) research, this study highlights the fact that that native speaker norms are still influential in the pre-service education programs in Turkey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in Atay's (2005) study, Turkish prospective teachers of English regarded having native-like competence as the main purpose of English language teaching, and reported that having a native teacher is more advantageous in order to develop a native-like accent. From a different perspective, exploring English language teacher education programs in Turkey, Cepik and Polat (2014) claimed that teacher educators expect teachers to have near-native proficiency in English. Confirming the results of Atay (2005) and Cepik and Polat's (2014) research, this study highlights the fact that that native speaker norms are still influential in the pre-service education programs in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…From a different perspective, exploring English language teacher education programs in Turkey, Cepik and Polat (2014) claimed that teacher educators expect teachers to have near-native proficiency in English. Confirming the results of Atay (2005) and Cepik and Polat's (2014) research, this study highlights the fact that that native speaker norms are still influential in the pre-service education programs in Turkey.…”
Section: Discussionmentioning
confidence: 99%